original article Good wine may need to mature: a critique of accelerated higher specialist training. Evidence from cognitive neuroscience. - Talbot M (Medical Education, 2004)
Higher specialist training in the UK is to be further shortened in the absence of any valid educational evidence for the wisdom of this move. Some practitioners/teachers are becoming increasingly concerned at this. Whereas the optimum length of time for such training is as yet undetermined, there is much in medical practice that resonates with the thinking of recent authors, who recommend slow incubation and facilitated reflection on experience, which steeps the learner in a hidden curriculum of practice, and entrains intuitive, 'slow mode' thinking. This engagement necessarily takes time. The author has surveyed some of the recent literature on problem solving, cognitive neuroscience, artificial intelligence and learning for practice, and discusses his conclusions. These are unsettling. Further truncation of the length of higher specialist training must be supported by robust educational evidence that supports this reduction. The author advises caution.